The impact of video gaming and playing a musical instrument on robotic surgical simulator performance - the Robotic Surgical Simulator Study (RS3) - Julia E. Hollmann; Julia Scholsching; Dennis Muensterer; Oliver J. Muensterer (Elsevier, 2024)
Background: A personal history of video gaming has been associated with improved laparoscopic skills acquisition in some but not all studies. The impact of playing a musical instrument on laparoscopic or robotic proficiency is less investigated. Methods: This study evaluates the impact of video gaming, playing a musical instrument, and other demographic parameters on robotic simulator proficiency in a cohort of 27 participants. Candidates performed 3 standardized exercises on a virtual reality robotic training platform, resulting in a proficiency score. After completing a detailed survey, participants repeated the standardized exercises to obtain a basic learning curve. Gaming history, playing a musical instrument, surgical experience, and demographic parameters were correlated with overall robotic proficiency and improvement during the experimental session. Results: Participants with previous gaming history had 33 % higher overall robotic performance scores (p = 0.02). There was no difference in performance between surgical trainees and attending physicians with high volume laparoscopic surgery experience (average of 77 laparoscopic procedures). In this small cohort, playing an instrument had no influence overall (p = 0.2), but we found a trend towards increased proficiency in those playing the piano, yielding 30 % higher scores (p = 0.14). Participants performed up to 22 % better in the second run of the ''Suture Sponge'' exercises (p = 0.08), indicating a steep learning curve of simulated robotic surgery. Conclusions: A history of video gaming and playing the piano is associated with improved performance on a virtual-reality robotic surgical simulator. The steep learning curve underlines the benefit of virtual robotic surgical training before performing robotic procedures on patients.